ANALISIS JARINGAN KOMUNIKASI DALAM AGROINDUSTRI KERIPIK UBI DI KELURAHAN SIALANG RAMPAI KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Jumiatun Jumiatun; Eri Sayamar; Yulia Andriani (Indonesian Journal of Agricultural Economics, 2018)
Sialang Rampai  Village is a center of cassava chips agroindustry in Pekanbaru City and cassava chips is a superior product in Sialang Rampai Village. One obstacle in cassava chips agroindustry is the lack of information on production technology and marketing. Therefore  to obtain the information needed, the craftmen of cassava chips will make communication relationships among craftsmen and with external actors in agroindustry who can provide information. The purposes of this research were: (1) to analyze the communication  network  about  the  production  of  cassava  chips  agroindustry  in  Sialang Rampai Village, Tenayan Raya district, Pekanbaru City.; (2) to analyze communication network about marketing of cassava chips agroindustry in Sialang Rampai Village, Tenayan Raya district, Pekanbaru City. The locations were selected intentionally and census was applied to interview 10 cassava chip craftsman who have product brand and business license. The results of this study indicate that in information about production, thirteen actors were involved in the communication network, namely ten sweet potato chips craftsmen and three external actors who provide the production facilities for cassava chip production. Stars in the communication network regarding production for internal actors was Mr. Sutarto and for external actors cassava farmers, groceries and firewood sellers. Whereas regarding marketing information, there were thirteen actors involved in the communication, ten actors of cassava chips craftsmen and three external actors which were the marketing institution of cassava chips. Stars in the communication network regarding marketing for internal actors was Mr Maswi and for external actors were the retailers.